Liver Resection after Downstaging Hepatocellular Carcinoma with Sorafenib. (20th February 2011) - Barbier, L.; Muscari, F.; Le Guellec, S.; Pariente, A.; Otal, P.; Suc, B.
Abstract : Background . Sorafenib is a molecular-targeted therapy used in palliative treatment of advanced hepatocellular carcinoma in Child A patients. Aims . To address the question of sorafenib as neoadjuvant treatment. Methods . We describe the cases of 2 patients who had surgery after sorafenib. Results . The patients had a large hepatocellular carcinoma in the right liver with venous neoplastic thrombi (1 in the right portal branch, 1 in the right hepatic vein). After 9 months of sorafenib, reassessment showed that tumours had decreased in size with a necrotic component. A right hepatectomy with thrombectomy was performed, and histopathology showed 35% to 60% necrosis. One patient had a recurrence after 6 months and had another liver resection; they are both recurrence-free since then. Conclusion . Sorafenib can downstage hepatocellular carcinoma and thus could represent a bridge to surgery. It may be possible to select patients in good general condition with partial regression of the tumour with sorafenib for a treatment in a curative intent.